已知f1(t)和f2(t)波形如下,若f(t)=f1(t)*f2(t),则f(0)=http://image.zhihuishu.com/zhs/onlineexam/ueditor/201906/e38151c6fa664a008f547dd1af821f92.bmp
举一反三
- 信号f1(t)和f2(t)如下图所示,f(t)=f1(t)*f2(t),则f(-1)等于http://image.zhihuishu.com/zhs/onlineexam/ueditor/201906/0749958f4da44655959aea343dbe4d9c.bmp
- 已知f1(t)和f2(t)波形如下,若f(t)=f1(t)*f2(t),则f(0)= A: 1 B: 2 C: 3 D: 4
- 已知f1(t)和f2(t)波形如下,若f(t)=f1(t)f2(t),则f(0)=
- 已知f1(t)和f2(t)波形如下,若f(t)=f1(t)*f2(t),则f(0...8f547dd1af821f92.bmp
- f1(t)和f2(t)波形如图所示,f(t)=f1(t)*f2(t),则f(2)等于_____。[img=289x135]1803c9ee6bcc58c.png[/img] A: 0.5 B: 1 C: 1.5 D: 2